Lack of Smoking Prevalence Data for Indigenous Peoples Worldwide Contributes to Epidemiological Invisibility - Marewa Glover (Data Science Journal)
The World Health Organization Framework Convention on Tobacco Control (FCTC) aims to facilitate global, regional and country-level efforts to reduce tobacco-related harm; however, evidence indicates that marginalised groups have been left behind by FCTC-directed programs. This study aimed to determine tobacco smoking prevalence among Indigenous Peoples worldwide. Countries with indigenous populations were identified, and online searches were conducted to determine reporting of smoking prevalence among Indigenous Peoples, national average smoking prevalence by gender, and commitment to the FCTC and United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP). Of the 105 countries identified to have Indigenous Peoples, only 5 (4.7%) government agencies conducted routine monitoring of tobacco use by ethnicity. Seventeen countries with a majority proportion of Indigenous People had national-level smoking prevalence data, which provided a useful first approximation for smoking prevalence. Sporadic, researcher-led studies reporting on smoking among some Indigenous Peoples existed in eight countries, but these were not comprehensive enough for meaningful statements about current smoking status to be made. Disaggregated reporting on tobacco use by ethnicity was suppressed or not acknowledged in nine countries and non-existent in 66 countries. The lack of data found in this study highlights the way in which the health of Indigenous People is sidelined through their general epidemiological invisibility.